RELIGION, IDENTITY AND MULTICULTURALISM: FINDING THE BALANCE BETWEEN SPIRITUALITY AND SOCIAL TOLERANCE - Zainuddin, Zainuddin; Amir, Bakhrum; Yani, Achmad (Khazanah: Jurnal Studi Islam dan Humaniora, 2025)
Abstract: This research explores the role of religion as a social identity marker in Indonesia's multicultural society through fieldwork in South Sumatra, specifically in Palembang and Musi Banyuasin. The current study utilizes a qualitative approach, incorporating in-depth interviews and participatory observation, to investigate the multifaceted nature of religious identity. The analysis reveals a dualistic function of religious identity, serving as a source of spirituality and a catalyst for social cohesion. However, the study also recognizes the potential for religious identity to catalyze exclusivism. Utilizing a combination of philosophical hermeneutics and a sociological perspective, this study highlights the significance of contextual interpretation of religious teachings in fostering inclusive spirituality. The findings indicate that tolerant spiritual expressions contribute to the strengthening of social harmony, as evidenced by increased interfaith engagement and reduced tensions. A model of spirituality-based multiculturalism is proposed as a strategy for improving social integration in Indonesia. Keywords: inclusive spirituality; religious identity; social harmony; multicultural society